2020
DOI: 10.18510/hssr.2020.8261
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic Approach to Principal’s Leadership and Its Impacts in Character Education Strengthening

Abstract: Purpose of the study: This paper aims to describe the basic reasons behind the application of the principal's humanistic approach, and the steps of the principal's humanistic approach to optimizing character education strengthening programs.Methodology: This research uses a qualitative approach, case study design. Data collection is done through in-depth interviews, participant observation, and study documentation to achieve research objectives. Main Findings:Research findings reveal that personal excellence (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…At the implementation level, both the human dimension and the professional dimension are in an equally important position. Therefore, moral and spiritual imagination explicitly opens the strategic steps of a servant leader's approach to giving meaning and direction to life together (Allen, et al 2016;Effendi et al, 2020). Principals have a moral obligation to carry out their duties responsibly to advance a shared vision (Focht, & Ponton, 2015;Waddock, 2016).…”
Section: Implementation Of Spiritual-moral Valuesmentioning
confidence: 99%
“…At the implementation level, both the human dimension and the professional dimension are in an equally important position. Therefore, moral and spiritual imagination explicitly opens the strategic steps of a servant leader's approach to giving meaning and direction to life together (Allen, et al 2016;Effendi et al, 2020). Principals have a moral obligation to carry out their duties responsibly to advance a shared vision (Focht, & Ponton, 2015;Waddock, 2016).…”
Section: Implementation Of Spiritual-moral Valuesmentioning
confidence: 99%
“…Thus, the transformative leadership of school principals in improving the quality of education can be achieved optimally to create quality educational institutions. (Rustan Effendi et al, 2020) Case study Describe the basic reasons behind implementing the school principal's humanistic approach and the steps of the school principal's humanistic process in optimizing character education strengthening programs.…”
Section: To Find Out and Analyze The Strategic Management Of Madrasah...mentioning
confidence: 99%
“…In addition, the humanistic approach has a positive impact on optimizing character-building programs in the school environment, such as well-organized extracurricular activities; the creation of a spirit of cooperation between teams so that they are solid and responsible at work; persuasive communication between principals, teachers, staff, school committee, parents, and the community; all parties support each other and are involved in every activity; faith values are getting stronger and more rigid; all components of the school have awareness and sensitivity to help each other, both related to learning activities and other interests; the high spirit of democratic life; establishing cooperation between schools and alumni to think about and build a better quality of education; Evaluation activities go well to reflect and internalize the meaning of each activity carried out (Rustan Effendi et al, 2020).…”
Section: Principal's Strategy In Improving the Quality Of Humanistic ...mentioning
confidence: 99%
“…In a similar vein, Wang, et al (2021) studied the effect of leaders' pro-social orientation on organizational affective commitment and organizational citizenship behavior and the study found that leaders' pro-social behavior which leaders are paying attention to the needs of employees has significantly affected the affective commitment and organizational citizenship behavior (OCB) This is also confirmed by the study of Vui-Yee (2016) whereby organizations that practice humanistic responsibility have a significant impact on employee commitment. In the context of educational institutions, Effendi et. al (2019) conducted a study concerning the effect of a humanistic approach to the principal's leadership on the strengthening of character education.…”
Section: Humanistic Leadershipmentioning
confidence: 99%